Clinical characteristics of chronic rhinitis following stroke - Choi, Jae Eun; Kim, Yeong Wook; Jee, Sungju; Sohn, Min Kyun (Frontiers in Neurology, 2023)
Background We previously observed that patients with stroke complained of rhinitis symptoms that developed following the occurrence of stroke. Objectives To investigate the relationship between chronic rhinitis (CR) and stroke. Methods This retrospective study analyzed the medical records and questionnaires of patients with stroke who visited our outpatient clinic from June to December 2020. Stroke lesions were mainly classified as supratentorial, infratentorial, and supra/infratentorial lesions. Supratentorial lesions were further divided into cortex, subcortex, and mixed. Participants were screened for CR and were subsequently divided into the CR and non-CR groups. The Sino-Nasal Outcome Test questionnaire and a questionnaire on autonomic nervous system symptoms were administered to all patients. Results Clinically evaluated indicators were not significantly different between the two groups. The number of patients with lesions in both the cortex and subcortex was significantly higher in the CR group than in the non-CR group. The risk of CR was higher in male patients with stroke than their female counterparts; additionally, the risk of CR was higher in patients with stroke who had both cortical and subcortical lesions, as well as autonomic dysfunction. Conclusions Individuals with subcortical stroke damage had a greater probability of developing CR. The risk was increased in men, as compared with that in women, when autonomic symptoms were present.